Controllable thermal conductivity in composites by constructing thermal conduction networks. (September 2021) - Guo, Yongqiang; Ruan, Kunpeng; Gu, Junwei
Abstract: Thermal conduction networks formed by thermally conductive fillers are crucial to the thermal conductivity coefficients ( λ ) of composites. In this paper, paraffin wax (PW) spheres with different sizes are prepared by instantaneous cooling granulation technology. With graphite coated on their surface by the micro-cladding method, the graphite/PW thermally conductive composites are then fabricated by hot pressing. The formation process of graphite thermal conduction networks at interfaces between the PW phases, and the influences of the density, distribution, and integrity of the networks on the λ of the graphite/PW composites are analyzed in-depth. Besides, an innovative concept of "Density of Thermal Conduction Networks ( D TCN )" is proposed to explain the λ difference among different graphite/PW composites. The D TCN of the graphite/PW composites have the best value for given graphite loading and molding pressure. The λ of the graphite/PW composites with the same size of PW spheres increases with increasing D TCN . When the amount of graphite is 10 wt%, the molding pressure is 200 MPa, and the PW spheres size is 2.08 ± 0.08 mm, the graphite/PW composites have the maximum λ (1.81 W/(m·K), the λ enhancement rate per unit mass fraction ( E λ/wt ) of graphite is 45, about 6 times of that of pure PW (0.33 W/(m·K)), also obviously higher than that of the freely dispersed R-graphite/PW composites with the same amount of graphite and molding pressure (0.79 W/(m·K), E λ/wt is 14). The higher D TCN, the more uniform distribution and integrity of the thermal conduction networks, and ultimately the higher λ of graphite/PW composites. Graphical abstract: Image 1 Highlights: Constructed controllable graphite thermal conduction networks at interfaces between the paraffin wax phases. Proposed innovative concept of "Density of Thermal Conduction Networks". Studied the influences of the thermal conduction networks on the thermal conductivity coefficients.